1997
DOI: 10.1084/jem.186.9.1487
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for Both Rac1 and Cdc42 in Membrane Ruffling and Phagocytosis in Leukocytes

Abstract: Specific pathways linking heterotrimeric G proteins and Fcγ receptors to the actin-based cytoskeleton are poorly understood. To test a requirement for Rho family members in cytoskeletal events mediated by structurally diverse receptors in leukocytes, we transfected the full-length human chemotactic peptide receptor in RAW 264.7 cells and examined cytoskeletal alterations in response to the chemotactic peptide formyl-methionyl-leucyl-phenylalanine (FMLP), colony stimulating factor–1 (CSF-1), IgG-coated particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
359
2
6

Year Published

1998
1998
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 405 publications
(383 citation statements)
references
References 28 publications
16
359
2
6
Order By: Relevance
“…This finding is similar to our observation that PAK1 can enhance the early phases of macropinocytosis in fibroblasts [S. Dharmawardhane and G. M. Bokoch, unpublished observations]. In leukocytes, Rac and Cdc42 have been shown to be required for phagocytosis [8]. PAK1 may act as one of the downstream effectors of Rac and Cdc42 in regulating the reorganization of the actin cytoskeleton to form phagocytic cups.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This finding is similar to our observation that PAK1 can enhance the early phases of macropinocytosis in fibroblasts [S. Dharmawardhane and G. M. Bokoch, unpublished observations]. In leukocytes, Rac and Cdc42 have been shown to be required for phagocytosis [8]. PAK1 may act as one of the downstream effectors of Rac and Cdc42 in regulating the reorganization of the actin cytoskeleton to form phagocytic cups.…”
Section: Discussionsupporting
confidence: 80%
“…When introduced into quiescent cells, activated forms of Rac1 and the related GTPase Cdc42 were shown to induce the formation of actin-rich membrane ruffles and filopodia, respectively [15,16]. Recent work has indicated that Rho GTPases may also play similar roles in regulating the cytoskeleton of highly motile cells such as leukocytes [8,9,17,18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The precise role of the proposed syk-PI3-kinase-racgelsolin cascade remains to be proven. However, syk, PI3-kinase, and rac are needed to complete phagocytosis (24,25,36,39,40). Rac appears to be specific for IgG-mediated phagocytosis and rho for complement-mediated phagocytosis (36), although a role for rho in Fc␥R-mediated phagocytosis has also been reported (41).…”
Section: Discussionmentioning
confidence: 99%